Photoshop CS5 bible - Dayley, Lisa DaNae; Dayley, Brad (Wiley Publishing, 2010)
An in-depth guide covers everything from the latest features and tools in Photoshop CS5 to the basics of Camera Raw, and includes techniques for producing images for mobile devices and creating 3D objects